Secreted Chaperones in Neurodegeneration - Chaplot, Kriti; Jarvela, Timothy S.; Lindberg, Iris (Frontiers in Aging Neuroscience, 2020)
Protein homeostasis, or proteostasis, is a combination of cellular processes that govern protein quality control, namely, protein translation, folding, processing and degradation. Disruptions in these processes can lead to protein misfolding and aggregation. Proteostatic disruption can lead to cellular changes such as endoplasmic reticulum or oxidative stress; organelle dysfunction; and, if continued, to cell death. A majority of neurodegenerative diseases involve the pathologic aggregation of proteins that subverts normal neuronal function. While prior reviews of neuronal proteostasis in neurodegenerative processes have focused on cytoplasmic chaperones, there is increasing evidence that chaperones secreted both by neurons and other brain cells in the extracellular - including transsynaptic- space play important roles in neuronal proteostasis. In this review, we will introduce various secreted chaperones involved in neurodegeneration. We begin with clusterin and discuss its identification in various protein aggregates, the use of increased CSF clusterin as a potential biomarker and as a potential therapeutic. Our next secreted chaperone is progranulin; polymorphisms in this gene represent a known genetic risk factor for frontotemporal lobar degeneration, and progranulin overexpression has been found to be effective in reducing Alzheimer’s- and Parkinson’s-like neurodegenerative phenotypes in mouse models. We move on to BRICHOS domain-containing proteins, a family of proteins containing highly potent anti-amyloidogenic activity; we summarize studies describing the biochemical mechanisms by which recombinant BRICHOS protein might serve as a therapeutic agent. The next section of the review is devoted to the secretory chaperones 7B2 and proSAAS, small neuronal proteins which are packaged together with neuropeptides and released during synaptic activity. Since proteins can be secreted by both classical secretory and non-classical mechanisms, we also review the small heat shock proteins (sHsps) that can be secreted from the cytoplasm to the extracellular environment, and provide evidence for their involvement in extracellular proteostasis and neuroprotection. Our goal in this review focusing on extracellular chaperones in neurodegenerative disease is to summarize the most recent literature relating to neurodegeneration for each secreted chaperone; to identify any common mechanisms; and to point out areas of similarity as well as differences between the secreted chaperones identified to date.